Analysis E344 using fluent / Ahmad Asfanizam Mohamad and Aizirizal Arshad - Mohamad, Ahmad Asfanizam; Arshad, Aizirizal (2000)
In this report some mathematical formulations of equation governing drag, lift and moment are presented. Some calculation method using Microsoft Excel are shown where it involved the calculation of the lift, drag and moment, also included are results in graphical visualization and graph.